Boron, nitrogen co-doped graphene: a superior electrocatalyst support and enhancing mechanism for methanol electrooxidation. (10th September 2016) - Sun, Yongrong; Du, Chunyu; Han, Guokang; Qu, Yunteng; Du, Lei; Wang, Yajing; Chen, Guangyu; Gao, Yunzhi; Yin, Geping
Graphical abstract: Highlights: Boron, nitrogen co-doped graphene was synthesized through simple thermal annealing. Pt/BNG catalyst exhibits high catalytic activity towards the MOR. The synergetic effects of support accelerate the methanol oxidation for Pt/BNG. The low CO adsorption energy promotes CO oxidation for Pt/BNG. Boron with lower electronegtivity doped graphene weakens the d-band center of Pt. Abstract: Boron, nitrogen co-doped graphene (BNG) is facilely synthesized by the two-step thermal annealing of graphene in the presence of melamine and boric acid, which is served as a novel support to enhance the catalytic properties of noble metal catalysts for the methanol oxidation reaction (MOR). It is revealed that the BNG support has more defect sites due to the co-doping of boron and nitrogen, so that uniformly dispersed Pt nanoparticles with average size of 2.3 nm are anchored on the surface of BNG support. The BNG supported Pt (Pt/BNG) catalyst exhibits excellent activity and improved stability towards the MOR, which is mainly attributed to the synergetic effects of boron and nitrogen co-doping into graphene support. It is revealed that nitrogen and boron co-doping produces more oxygen-containing species, which accelerates the methanol oxidation by the so-called bifunctional mechanism. Moreover, the boron doping weakens the adsorption energy of poisoning intermediates on Pt surface by lowering the d-band center of Pt, facilitating the oxidative removal of poisoning intermediates and methanol oxidation. The boron and nitrogen co-doping of graphene opens up a new strategy for the catalyst performance optimization.